Pengelolaan Saluran Irigasi Guna Meningkatkan Produktivitas Pertanian di Desa Jubel Kidul - Prima Eko Agustyawan; Alma Amalia Sabilla (Pendidikan Matematika, FKIP Universitas Mataram, 2021)
Agriculture is a sector of economic development considering its function and role in providing food for the population, as well as the place where the livelihoods of the residents of Jubelkidul Village depend. To increase food yields, irrigation network management was held in Jubelkidul Village. Irrigation is the most important thing in the food production process. The development of the Jubelkidul irrigation area is carried out with the aim of maintaining the sustainability of irrigation water supply in the Jubelkidul area. Efforts that can be made to maintain the sustainability of the function of the irrigation area of ​​Jubelkidul Village in supporting increased agricultural yields are participatory management of irrigation areas through institutional empowerment of water-using farmers. agriculture in Jubelkidul Village. This research is descriptive qualitative research with survey method. The research location is the Jubelkidul irrigation area which includes 5 hamlets in the Sugio sub-district. The types of data used are primary and secondary data collected by field observations, and interviews. The results show that the irrigation management of Jubelkidul village on water use is influenced by the dimensions of location, time and certain qualities.